Implicit followership theory to employee creativity: The roles of leader–member exchange, self-efficacy and intrinsic motivation. (10th July 2017) - Kong, Ming; Xu, Haoying; Zhou, Aiqin; Yuan, Yue
Abstract: Leaders' implicit followership theory describes leaders' personal assumptions about the traits and behaviors that characterize followers. Unlike traditional organizational behavior research, studies on leaders' implicit followership theory can deepen our understandings of 'how leaders and followers perceive, decide and take action' from follower-centric perspective. Adopting 267 follower–leader dyads from 16 Chinese enterprises as our final sample, we found that: (1) positive leaders' implicit followership theory had significant positive effect on followers' creativity; (2) followers' leader–member exchange with leader, intrinsic motivation and creative self-efficacy mediated the positive relationship between positive leaders' implicit followership theory and followers' creativity; (3) no significance difference was found between the mediating effects of leader–member exchange, intrinsic motivation and creative self-efficacy. The current study not only extended the application of social cognitive theory in leadership research, but also made contributions to the enrichment of social exchange theory and componential theory of creativity.